Are Spanish Children Taking Advantage of their Weekly Classroom Time? - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Springer Nature, 2018)
There is a common belief in Spain that a large amount of classroom time is supposed to be an indicator of better academic achievement, due to children’s prolonged exposure to the teaching-learning process. Nevertheless, international evi dence does not seem to support this concept, as the amount of weekly instruction hours that children receive in Spain is well above the one provided in other countries, which clearly perform better than Spain in international assessments. Because of that, this current research proposes to analyse two issues regarding weekly instruction time: firstly, whether or not instruction time per week affects the academic achievement of Spanish children; secondly, if this potential effect differs across Spanish regions Autonomous Communities–. In order to do that, we have made use of student fixed effects between-subjects to obtain the potential causal effect of weekly instruction time on students’ academic achievement. The main results of this analysis have indicated that, in general for Spain, weekly instruction time does not seem to affect children’s academic achievement. However, this lack of influence may reflect the compensation of different effects of instruction time per week on students’ academic achievement for some Spanish Autonomous Communities–concretely, Catalonia, Navarra and the Basque Country–. In the view of these results, we propose some policy interventions. We also highlight the importance of studying each country’sparticularcaseinrespect to this instruction time issue, as it may present different effects in each country.
https://openpolicyfinder.jisc.ac.uk/id/publication/16473
Keywords: Rendimiento académico - Modelos matemáticos; Motivación en educación; Weekly instruction time; Indicators of academic achievement; Spanish regions; Student fixed effects; Secondary education